Interpreting SIMDA Next-G Implementation in Local Government: An Ethnomethodological Study - Restiany Restiany; Sokarina Ayudia; Waskito Iman (Cita Konsultindo Research Center, 2023)
This study aims to interpret the implementation of SIMDA Next-G in BPKAD in West Sumbawa Regency. This study uses ethnomethodology. Data collection techniques were used in this study through observation, interviews, and documentation. The informants from this study is a Head of the Sub-Sector of Accounting Reporting in the Accounting Sector at BPKAD in West Sumbawa Regency. The results of this study indicate that the implementation of SIMDA Next-G in the local government of West Sumbawa Regency needs to run more effectively, even though the information system should be able to help improve the quality of financial reports. It happens for several reasons—first, using 2 (two) applications. Second, the input process takes longer due to using a website-based application and no longer a desktop, such as SIMDA Finance. However, the quality of the resulting financial reports is better than SIPD. Problems that often arise when using SIPD, such as data that has been input are lost or deleted, and the appearance of anomalous data affects the quality of existing financial reports. Several menus, such as the general cash book and cash ledger, also cannot be used.